2019 International Conference on High Performance Computing &Amp; Simulation (HPCS) 2019
DOI: 10.1109/hpcs48598.2019.9188065
|View full text |Cite
|
Sign up to set email alerts
|

Surrogate-Assisted Optimization for Multi-stage Optimal Scheduling of Virtual Power Plants

Abstract: This paper presents a comparison between two surrogate-assisted optimization methods dealing with two-stage stochastic programming. The Efficient Global Optimization (EGO) framework is challenging a method coupling Genetic Algorithm (GA) and offline-learnt kriging model for the lower stage optimization. The objective is to prove the good behavior of bayesian optimization (and in particular EGO) applied to a real-world two-stage problem with strong dependencies between the stages. The problem consists in determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In a PC, parallel computing is already used inside the simulator (Abaqus) in order to reduce the computation time of a single simulation. Then, sequential EGO is preferred to parallel versions [27,50].…”
Section: Optimization Methodologymentioning
confidence: 99%
“…In a PC, parallel computing is already used inside the simulator (Abaqus) in order to reduce the computation time of a single simulation. Then, sequential EGO is preferred to parallel versions [27,50].…”
Section: Optimization Methodologymentioning
confidence: 99%
“…where K = Φ T ΣΦ is known as the covariance matrix and K (1)(2) = Φ(x (1) ) T ΣΦ(x (2) ) = k x (1) , x (2) . The k function is referred to as the covariance kernel and K = (k(x i , x j )) i,j∈{1,...,n} and is chosen as an hyper-parameter.…”
Section: A Gaussian Process Regressionmentioning
confidence: 99%
“…However, in modern competitive energy networks, individual actors rely on efficient operational strategies, enabling them to hedge the uncertainty of renewable energy resources. It is thus essential to dispose of efficient tools to take informed decisions at the different time steps of the energy markets (e.g., from long-term towards real-time) [2]. Let us assume that for a decision x ∈ R d , the expected profit of a UPHES operator is given by f : R d → R; x → y = f (x).…”
Section: Introductionmentioning
confidence: 99%
“…However, in modern competitive energy networks, individual actors rely on efficient operational strategies, enabling them to hedge the uncertainty of renewable energy resources. It is thus essential to dispose of efficient tools to make informed and fast decisions at the different time steps of the energy markets (e.g., from long-term towards real-time) [2]. From the operator's point of view, the quality of a decision is measured as a profit, so let us assume that for a decision x ∈ R d , the expected profit of a UPHES operator is given by f : R d → R; x → y = f (x).…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, surrogate-based optimization has never been applied to the UPHES scheduling problem. In our previous work [2], we demonstrated that Bayesian Optimization (BO) can be handy in management problems in electrical engineering.…”
Section: Introductionmentioning
confidence: 99%